Lithium niobate negative electrode material, preparation method thereof and all-solid-state lithium ion battery
By using lithium niobate negative electrode material in lithium-ion batteries, the core-shell structure is used to improve the interface problem between silicon and sulfide electrolyte, and the volume expansion of silicon is suppressed, and the performance attenuation problems caused by the interface problem and volume expansion in lithium-ion batteries are solved, thereby achieving higher cycling performance and rate performance.
Patent Information
- Application Number
- CN202411807646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-08
AI Technical Summary
In existing lithium-ion batteries, there is an interface problem between silicon and sulfide electrolyte, which causes lithium ions to be reduced on the surface of low-potential silicon to form lithium metal deposition, forming lithium dendrites, which in turn causes capacity attenuation and short circuit problems. At the same time, the volume expansion of silicon during the cycle, resulting in the continuous deterioration of contact with sulfide electrolyte, affecting battery performance.
Lithium niobate negative electrode material is used, which has a core-shell structure, with silicon as a core and lithium niobate as a shell. By uniformly coating silicon and lithium niobate, lithium niobate negative electrode material is formed, which improves the interface problem between silicon and sulfide electrolyte and inhibits the volume expansion of silicon.
Through the use of lithium niobate negative electrode material, the circulation and safety performance of lithium-ion batteries are improved, the impact of silicon volume expansion on the electrode structure is reduced, the contact failure between the negative electrode material and the sulfide solid electrolyte is reduced, and the rate performance and cycle stability of the battery are improved.
Smart Images

Figure CN119786588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium niobate negative electrode material and a preparation method thereof, and an all-solid-state lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely explored as a highly efficient electrochemical energy storage device. In order to further improve their energy density and power density and reduce their production costs so that they can be used on a large scale in power transmission and energy storage, it is of great significance to develop a new generation of batteries. Sulfide all-solid-state lithium batteries are based on non-flammable sulfide solid electrolytes and are expected to improve energy density and alleviate safety issues through a unique bipolar stacking method. However, batteries based on traditional graphite anodes have reached the theoretical limit of energy density. The use of high-capacity electrode materials is an urgent need for the development of high-energy sulfide all-solid-state lithium batteries.
[0003] As a negative electrode material, silicon (Si) is expected to replace graphite with its ultra-high specific capacity, suitable platform potential and abundant natural resources. After 20 years of efforts, its feasibility in the lithium-ion battery industry is still unsatisfactory. There are interface problems between silicon and sulfide electrolytes. During the cycle, lithium ions will be reduced on the low-potential silicon surface to generate lithium metal deposited on the silicon surface, generating lithium dendrites, which can easily lead to capacity decay and short circuit problems. Silicon will also undergo a large volume expansion during the cycle, and the contact with the sulfide electrolyte will continue to deteriorate; as the cycle progresses, the volume expansion of silicon during lithium insertion and delithiation is about 300%, resulting in the continuous expansion of the gap between silicon and the sulfide solid electrolyte, and the contact between the two is constantly deteriorating, which makes the electron and ion transmission between the two deteriorate, resulting in rapid performance decay. With the formation of lithium-silicon alloy, the volume of the silicon anode changes dramatically. More importantly, the continuous rearrangement of the solid electrolyte interface (SEI) layer consumes a large amount of active lithium from the counter electrode, resulting in a rapid decrease in capacity, especially in full batteries with very limited lithium resources.
[0004] Therefore, it is necessary to provide a lithium niobate negative electrode material and a preparation method thereof and an all-solid-state lithium-ion battery to improve the interface problem between silicon and sulfide electrolyte, inhibit the volume expansion of silicon, and at the same time improve the rate performance and cycle stability of the battery. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a lithium niobate negative electrode material and a preparation method thereof and an all-solid-state lithium-ion battery, which improve the interface problem between silicon and sulfide electrolyte, inhibit the volume expansion of silicon, and at the same time improve the rate performance and cycle stability of the battery.
[0006] A first aspect of the present invention provides a lithium niobate negative electrode material.
[0007] Specifically, it has a core-shell structure, wherein the core comprises silicon; the shell comprises lithium niobate; and the silicon D 50 0.03~50μm.
[0008] Preferably, the silicon accounts for 80-95% of the total mass of the lithium niobate negative electrode material.
[0009] Further preferably, the silicon accounts for 85-95% of the total mass of the lithium niobate negative electrode material.
[0010] More preferably, the silicon accounts for 90% of the total mass of the lithium niobate negative electrode material.
[0011] Preferably, the shell has a thickness of 5 to 100 nm.
[0012] Preferably, the silicon D 50 0.03~50μm.
[0013] Further preferably, the silicon D 50 The particle size of the silicon core is at least one of 0.03 μm, 0.05 μm, 0.1 μm and 50 μm. A suitable silicon core particle size can achieve a smaller porosity control.
[0014] A second aspect of the present invention provides a method for preparing a lithium niobate negative electrode material.
[0015] Specifically, the following steps are included:
[0016] (1) adding silicon, a lithium source and a niobium source into a solvent, stirring and mixing to obtain a mixture;
[0017] (2) after removing the solvent from the mixture, the mixture is placed in a vacuum oven and heated under vacuum to obtain a solid powder;
[0018] (3) The solid powder is calcined under a protective atmosphere to obtain a lithium niobate negative electrode material.
[0019] Preferably, in step (1), the lithium source includes at least one of lithium carbonate and lithium acetate.
[0020] Preferably, in step (1), the niobium source includes at least one of niobium pentoxide and niobium hydroxide.
[0021] Preferably, in step (1), the molar ratio of the lithium source to silicon is 0.5 to 5:100.
[0022] Further preferably, in step (1), the molar ratio of the lithium source to silicon is 1 to 5:100.
[0023] More preferably, in step (1), the molar ratio of the lithium source to silicon is 1:100.
[0024] Preferably, in step (1), the molar ratio of the niobium source to the lithium source is 95-105:100.
[0025] Further preferably, in step (1), the molar ratio of the niobium source to the lithium source is 95-100:100.
[0026] More preferably, in step (1), the molar ratio of the niobium source to the lithium source is 100:100.
[0027] Preferably, in step (1), the stirring and mixing is performed at a speed of 300 to 800 rpm and for a time of 0.1 to 1 h.
[0028] Further preferably, in step (1), the stirring and mixing is performed at a speed of 500 to 800 rpm and for a time of 0.5 to 1 h.
[0029] More preferably, in step (1), the stirring and mixing is performed at a rotation speed of 600 rpm and for a time of 0.5 h.
[0030] Preferably, in step (2), the vacuum heating temperature is 60 to 100° C., the pressure is -0.04 to -0.1 MPa, and the time is 1 to 72 hours.
[0031] Preferably, in step (2), the vacuum heating temperature is 75 to 85° C., the pressure is -0.08 to -0.1 MPa, and the time is 6 to 18 hours.
[0032] More preferably, in step (2), the vacuum heating is performed at a temperature of 80° C., a pressure of -0.1 MPa, and a time of 12 h.
[0033] Preferably, in step (2), the water removal method includes at least one of rotary evaporation, freeze drying, and centrifugal washing.
[0034] Further preferably, in step (2), the water removal method is rotary evaporation.
[0035] Preferably, in step (3), the calcination temperature is 400 to 1000° C., and the calcination time is 1 to 24 hours.
[0036] Further preferably, in step (3), the calcination temperature is 400-800° C., and the calcination time is 1-12 h.
[0037] More preferably, in step (3), the calcination temperature is 600-800° C., and the calcination time is 1-5 h.
[0038] Preferably, in step (3), the protective atmosphere includes at least one of argon, helium and nitrogen.
[0039] A third aspect of the present invention provides a negative electrode.
[0040] Specifically, the negative electrode includes the lithium niobate negative electrode material provided in the first aspect.
[0041] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery.
[0042] Specifically, the all-solid-state lithium-ion battery includes the negative electrode provided by the third aspect.
[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0044] The lithium niobate negative electrode material of the present invention has lithium niobate uniformly distributed on its surface, which can achieve excellent contact with the sulfide solid electrolyte. The lithium storage capacity of lithium niobate can reduce lithium deposition and the formation of lithium dendrites, and improve the cycle performance and safety performance of all-solid-state lithium-ion batteries. The low expansion shell of the lithium niobate material can reduce the effect of silicon volume expansion on the electrode structure, inhibit the increase of porosity in the composite negative electrode, reduce the contact failure between the negative electrode material and the sulfide solid electrolyte, improve the problem of accelerated capacity attenuation of the material during long-term circulation, and improve the rate performance of the all-solid-state lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The SEM image and EDS detection image of the lithium niobate negative electrode material prepared in Example 1 of the present invention;
[0046] Figure 2 This is an EDS test image of the lithium niobate negative electrode material prepared in Comparative Example 2 of the present invention;
[0047] Figure 3 This is a rate performance diagram of the all-solid-state lithium-ion battery composed of Example 1 of the present invention. DETAILED DESCRIPTION
[0048] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0049] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0050] Example 1
[0051] A lithium niobate negative electrode material and a preparation method thereof.
[0052] The lithium niobate negative electrode material has a core-shell structure, the core is composed of silicon; the shell is composed of lithium niobate; silicon accounts for 90% of the total mass of the lithium niobate negative electrode material; the thickness of the lithium niobate shell is 5nm, and the D 50 is 100nm.
[0053] The specific preparation method is as follows:
[0054] (1) 0.1 mol D 50 Silicon with a size of 100 nm was dissolved in 100 mL of anhydrous ethanol, and dispersed by ultrasonic stirring to obtain a dispersion of the silicon material, and then 0.001 mol of lithium carbonate and 0.001 mol of niobium pentoxide were added to the dispersion, and stirred and mixed at 600 rpm for 0.5 h to obtain a mixture;
[0055] (2) After removing anhydrous ethanol from the mixture by rotary evaporation, the mixture was placed in a vacuum oven and heated at 80° C. and −0.1 MPa for 12 h to obtain a solid powder;
[0056] (3) The solid powder was calcined in argon, heated to 600°C at a heating rate of 5°C / min and maintained for 3 hours, washed with deionized water, and then vacuum dried at 80°C and -0.1 MPa for 24 hours to obtain a lithium niobate negative electrode material.
[0057] Example 2
[0058] A lithium niobate negative electrode material and a preparation method thereof.
[0059] The difference from Example 1 is that niobium pentoxide in the preparation method is replaced by niobium hydroxide.
[0060] Example 3
[0061] A lithium niobate negative electrode material and a preparation method thereof.
[0062] The difference from Example 1 is that the calcination temperature in the preparation method is 800°C.
[0063] Comparative Example 1
[0064] A lithium niobate negative electrode material and a preparation method thereof.
[0065] The difference from Example 1 is that the calcination temperature in the preparation method is 200°C.
[0066] Comparative Example 2
[0067] A lithium niobate negative electrode material and a preparation method thereof.
[0068] The difference from Example 1 is that the lithium carbonate in the preparation method is replaced by lithium phosphate.
[0069] Comparative Example 3
[0070] A lithium niobate negative electrode material and a preparation method thereof.
[0071] The difference from Example 1 is that the D of silicon in the preparation method is 50 is 100μm.
[0072] Comparative Example 4
[0073] A lithium niobate negative electrode material and a preparation method thereof.
[0074] The difference from Example 1 is that the amount of lithium carbonate used in the preparation method is 0.01 mol.
[0075] Performance testing:
[0076] 1. Scanning electron microscope and energy dispersive X-ray spectroscopy.
[0077] The lithium niobate negative electrode material prepared in Example 1 was subjected to scanning electron microscopy (SEM) testing and energy dispersive X-ray spectroscopy (EDS) testing. The results are as follows: Figure 1 As shown; the lithium niobate negative electrode material prepared in Comparative Example 2 was subjected to energy dispersive X-ray spectroscopy (EDS) detection, and the results are as follows Figure 2 shown.
[0078] Through SEM testing, Figure 1 It can be seen that the material prepared in Example 1 is composed of a core silicon and an outer shell lithium niobate. The small lithium niobate particles are evenly distributed on the silicon surface, tightly coating the silicon, which can effectively reduce the contact between silicon and the sulfide solid electrolyte and improve the lithium conductivity of the material.
[0079] Comparative Example 2 ( Figure 2 ) There is no niobium element at all, and there is a clear phenomenon of lithium niobate not being coated. This is attributed to the fact that lithium phosphate and niobium pentoxide are difficult to react and form lithium niobate, so they cannot be uniformly attached to the silicon surface to form a lithium niobate coating layer.
[0080] 2. Electrochemical performance test:
[0081] The lithium niobate negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were used as active materials, and each active material was mixed with LiP6S5Cl and polytetrafluoroethylene in a mass ratio of 60:40:1 to form a composite negative electrode, and a negative electrode sheet was obtained through a roller pressing and slicing process. The negative electrode sheet was placed in a polyetheretherketone tube with a diameter of 10 mm, and then 100 mg of LiP6S5Cl was weighed and added to the tube, and pressed and formed at a pressure of 12 MPa and tightly contacted with the negative electrode sheet, and finally an indium sheet and a lithium sheet were added to the other side of the solid electrolyte, and pressed and formed at a pressure of 360 MPa to prepare an all-solid-state lithium-ion battery with a three-layer structure (composite negative electrode / solid electrolyte / Li-In alloy).
[0082] (1) Electrochemical impedance spectroscopy:
[0083] The internal resistance of the half-cell was tested by electrochemical impedance spectroscopy (EIS), thereby determining the contact between the obtained negative electrode material and the sulfide solid electrolyte and the lithium conductivity. The internal resistance of the all-solid-state lithium-ion battery composed of the lithium niobate negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 is shown in Table 1.
[0084] Table 1 Internal resistance results of all-solid-state lithium-ion batteries composed of Examples 1 to 3 and Comparative Examples 1 to 4
[0085]
[0086] By comparing the internal resistance of the all-solid-state lithium-ion battery composed of the lithium niobate negative electrode material prepared in Examples 1 to 3 and Comparative Examples 1 to 4, it can be found that Example 1 has the best contact with the sulfide solid electrolyte, and the combination of the two achieves a better and lowest internal resistance, which is conducive to the transmission of lithium ions in the negative electrode, thereby achieving a higher rate performance. Example 1 better achieves the coating of silicon material by lithium niobate, effectively inhibiting the contact between silicon and the sulfide solid electrolyte, and at the same time, lithium niobate as an intermediate layer can quickly transfer lithium ions.
[0087] (2) First Coulomb efficiency test:
[0088] The first coulombic efficiency (first efficiency) test was carried out on the all-solid-state lithium-ion batteries composed of Examples 1 to 3 and Comparative Examples 1 to 4. Each all-solid-state lithium-ion battery was charged and discharged at a rate of 0.1C. The first coulombic efficiency = first discharge capacity / first charge capacity × 100%. The results are shown in Table 2.
[0089] Table 2 First performance test results of all-solid-state lithium-ion batteries composed of Examples 1 to 3 and Comparative Examples 1 to 4
[0090]
[0091] By comparing the first effects of the all-solid-state lithium-ion batteries composed of the lithium niobate negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4, it can be seen that the first effect of Example 1 is the highest, indicating that the lithium niobate coating on its surface is the most uniform, and the uniformly coated lithium niobate effectively reduces the contact between silicon and the sulfide solid electrolyte, so the side reaction of silicon and the sulfide solid electrolyte is correspondingly reduced, and the first effect is improved.
[0092] (3) Rate performance test:
[0093] The rate performance test of the all-solid-state lithium-ion battery composed of Example 1 was carried out, and the test conditions were as follows: The test conditions were rate performance at different current densities: each all-solid-state lithium-ion battery was charged and discharged at 60°C with currents of 0.1C, 0.3C, 0.5C, 0.8C and 1C and a cut-off voltage of -0.61 to 0.2V. The battery was tested under a pressure of 15MPa. The results are as follows: Figure 3 As shown. Example 1 shows excellent rate performance, and can even maintain a specific capacity of 2667 mAh / g at a rate of 1 C. This fully proves that the lithium niobate negative electrode material prepared by the present invention has excellent performance and commercial potential.
[0094] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.
Claims
1. A lithium niobate negative electrode material, characterized in that: It has a core-shell structure, wherein the core is composed of silicon and the shell is composed of lithium niobate; The silicon D 50 0.03~50μm.
2. The lithium niobate negative electrode material according to claim 1, characterized in that: The silicon accounts for 80-95% of the total mass of the lithium niobate negative electrode material.
3. The lithium niobate negative electrode material according to claim 1, characterized in that: The shell has a thickness of 5 to 100 nm.
4. The method for preparing the lithium niobate negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) adding silicon, a lithium source and a niobium source into a solvent, stirring and mixing to obtain a mixture; (2) after removing the solvent from the mixture, the mixture is placed in a vacuum oven and heated under vacuum to obtain a solid powder; (3) The solid powder is calcined under a protective atmosphere to obtain a lithium niobate negative electrode material.
5. The preparation method according to claim 4, characterized in that: In step (1), the niobium source includes at least one of niobium pentoxide and niobium hydroxide.
6. The preparation method according to claim 4, characterized in that: In step (1), the molar ratio of the lithium source to silicon is 0.5 to 5:
100.
7. The preparation method according to claim 4, characterized in that: In step (1), the molar ratio of the niobium source to the lithium source is 95-105:
100.
8. The preparation method according to claim 4, characterized in that: In step (3), the calcination temperature is 400 to 1000° C., and the calcination time is 1 to 24 hours.
9. A negative electrode, characterized in that The negative electrode comprises the lithium niobate negative electrode material according to any one of claims 1 to 3.
10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the negative electrode according to claim 9.
Citation Information
Patent Citations
Solid electrolyte composition, solid electrolyte-containing sheet, all-solid-state secondary battery, method for producing solid electrolyte composition, method for producing solid electrolyte-containing sheet, and method for manufacturing all-solid-state secondary battery
CN108780918A
Lithium niobite / niobium-base oxide / silicon compound cathode material, preparation method and application thereof
CN108899517A
Silicon-based negative electrode material, preparation method and application thereof, and lithium ion battery
CN117438587A
Cited By
Desolvation layer modified silicon-carbon negative electrode and preparation method thereof
CN120413631A